Sosyal Medya’nın Kaldıraç Etkisi: Türk Sivil Havacılık Endüstrisi Sosyal Medya Gücünü Nasıl Kullanıyor? - Kara, Tolga (The Turkish Online Journal of Design Art and Communication, 2016)
After the advent of the internet, communication methods have sharply changed and interactivity become more important for customers. Especially customer activities such as information search for company or product details, using online services such as purchase or engaging in social networks in online communities are continue to rise. Aim of this study is to demonstrate how Turkish Civil Aviation Industry use social media tools such as Facebook, Twitter, YouTube, and Blogs and others, while they are trying to create competitive advantages in Turkey. Based on the coding schema, we analyze their usage types.
Keywords: Sosyal Medya; Havacılık Endüstrisi; Sosyal Ticaret; Social Media; Aviation Industry; Social Commerce